Sociodemographic characterization of dental prosthesis users in the state of Amapá (Research, Society and Development, 2020)
The number of people with no teeth is growing in Brazil, 11% of the population is totally toothless, corresponding to an amount of 16 million people and 33% of the population uses some type of dental prosthesis. Based on these relevant numbers, the objective of this study were to perform the sociodemographic characterization of total edentuli using mucosal-supported total dentures and implant-supported total dentures in the city of Macapá, state of Amapá, Brazil. We interviewed 299 users of mucosal-supported total dentures and 48 users of implant-supported total dentures using a structured sociodemographic questionnaire already validated by the medical literature. The study variables were characterized by descriptive statistical measures. As descriptive evaluations were used the mean and standard deviation for the characterization of quantitative variables and absolute and relative frequencies for the characterization of qualitative and quantitative variables. The most prevalent age group was 61 to 70 years for both groups. Regarding gender, they presented 50% of men and women, respectively; in implant-supported prosthesis users, while 56% of mucosupported prosthesis users were women, 69% of implant-supported prosthesis users declared themselves white; 44% had completed higher education, with a family income of 7 to 10 minimum wages, 65%. Among the users of mucosal-supported prosthesis, 69% declared themselves white, most with a high school degree, 62%, and a family income of 1 to 2 minimum wages, 69%. It was concluded that users of implant-supported prosthesis presented significantly higher level of education and higher family income.